PEMBELAJARAN MENULIS TEKS ULASAN PADA SISWA KELAS VIII DENGAN MENGGUNAKAN MODEL DISCOVERY LEARNING BERBANTUAN APLIKASI CANVA - M Agung Maulana; Teti Sobari; R Mekar Ismayani (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Creating review texts that analyze and evaluate both literary and non-literary works. At the junior high school level, review text learning—which provides reviews and evaluations of literary or non-literary works—is studied. However, it occurs from the review text learning activities based on observations made during field experience practice that composing review texts is still done conventionally, necessitating the need for innovative learning strategies involving applications. The discovery learning methodology, supported by the Canva application, is one of them. The goal of this study was to ascertain how students responded and what they learned when they used the discovery learning methodology with the Canva software to write review texts. A program called Canva that supports learning has tools for making review texts more creative. The technique employed is a descriptive qualitative method, and tests and questionnaires are used to collect the data. The outcomes of assessments and questionnaires that use average values and satisfy the achievement markers can be used to determine whether learning has been successful. The test scores were 78.8 and the questionnaire was 63%, according to the research findings. So, the discovery learning paradigm supported by the Canva application can enhance students' learning to create review texts, based on student learning outcomes and student response results.